2012
DOI: 10.1128/jb.00361-12
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Biofilm Development Depends on the Phosphorylation Status of RcsB

Abstract: The Rcs phosphorelay pathway is a complex signaling pathway involved in the regulation of many cell surface structures in enteric bacteria. In response to environmental stimuli, the sensor histidine kinase (RcsC) autophosphorylates and then transfers the phosphate through intermediary steps to the response regulator (RcsB), which, once phosphorylated, regulates gene expression. Here, we show that Salmonella biofilm development depends on the phosphorylation status of RcsB. Thus, unphosphorylated RcsB, hitherto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 62 publications
3
51
1
1
Order By: Relevance
“…1C). We did not observe the previously reported RprA-mediated repression of csgD (35,36), perhaps because the csgD promoter was silent under the experimental conditions used here (37). This notwithstanding, our pulse expression data suggested that the two forms of RprA recognize several targets by different seed regions and predicted processed RprA to be a regulator in its own right.…”
Section: Resultscontrasting
confidence: 46%
“…1C). We did not observe the previously reported RprA-mediated repression of csgD (35,36), perhaps because the csgD promoter was silent under the experimental conditions used here (37). This notwithstanding, our pulse expression data suggested that the two forms of RprA recognize several targets by different seed regions and predicted processed RprA to be a regulator in its own right.…”
Section: Resultscontrasting
confidence: 46%
“…S1, supplementary file). A decreased expression of csgA as a result of a diminished expression of csgD, has been reported earlier in S. Typhimurium (Baugh et al, 2012;Latasa et al, 2012). Additionally, the expression of csgA was significantly increased in the clinical isolate compared with the reference wild type strain.…”
Section: Discussionmentioning
confidence: 58%
“…Briefly, 1 colony-forming unit of Salmonella was grown in 5 ml of LBNaCl−, pH 7.0, at 28°C and 200 rpm for 12 h, in 15 ml glass tubes. Agitation was stopped and static cultures were tested visually and photographed by a digital camera every 24 h for 72 h. Biofilm development was visualized as a floating pellicle at the air -broth interface (Latasa et al, 2012). The following scoring scheme was first described by Cisar et al (1979) and adapted for this work: 0, no pellicle formation; 1, very small and non-uniform pellicle; 2, easily visible pellicle that can be dispersed by shaking; 3, clearly visible pellicle non-dense which cannot be dispersed by shaking; and 4, dense pellicle which totally blocks the surface of the culture and cannot be dispersed by shaking.…”
Section: Phenotypic Assays For Biofilm Formationmentioning
confidence: 99%
“…In some cases, the unphosphorylated form of a response regulator has been shown to specifically activate gene expression at some target-promoters (e.g. 58,59). However, in the case studied here, our results suggest that at least some OmpR-P is required for transcription activation at the Omr promoters.…”
Section: Discussionmentioning
confidence: 99%